Genes and MicroRNAs Associated with Mouse Cleft Palate: A Systematic Review and Bioinformatics Analysis - Suzuki, Akiko (Mech Dev, 2018)
Cleft palate (CP) is the most prevalent craniofacial deformity, with ethnic and geographic variation in prevalence in humans. Mice have been used as an animal model to study the cause(s) of CP by several approaches, including genetic and chemical-induced approaches. Mouse genetic approaches revealed that significant amounts of genes are involved in the CP pathology. The aim of this study was to identify common features of CP-associated genes and to explore the roles of microRNAs (miRNAs) as important post-transcriptional regulators that may be involved in the regulation of CP genes. To generate an accurate list of genes associated with CP, we first conducted systematic literature searches through main databases such as Medline, Embase, and PubMed, as well as other sources such as Scopus and Mouse Genome Informatics. We found that 195 mouse strains with single-gene mutations and 140 mouse strains with compound-gene mutations were reported to have CP. The CP genes were categorized by functions and pathways using the Kyoto Encyclopedia of Genes and Genomes and Gene Ontology annotations, highlighting the contribution of cellular metabolism to CP. A total of 18 miRNAs were involved in the regulation of multiple CP genes. Human genotype-phenotype analysis revealed that variants in five human homologous CP genes (IRF6, FOXE1, VAX1, WNT9B, and GAD1) significantly contributed to the human CP phenotype. Thus, our results suggest that cellular metabolism and miRNAs play an important role in the regulation of genetic pathways and networks crucial for palatal formation.